New biomarkers for diagnosis of bladder cancer: a bibliometric analysis - Roberto Falabella; Valentina De Simone; Felice Crocetto; Francesco Del Giudice; Angelo Porreca; Nazario Foschi; Biagio Barone; Luca Di Gianfrancesco; Valentina Di Pasquale; Vincenzo Francesco Caputo (Archivio Italiano di Urologia e Andrologia)
Background/Objectives: Bladder cancer is a multifactorial disease, ranking as the 10th most common cancer globally and the fourth most common cancer in men and the ninth in women in the Western world. This bibliometric analysis aims to identify and evaluate scientific literature addressing new biomarkers for bladder cancer diagnosis, as well as to identify the most prolific organizations, authors, journals, countries, and keywords within this research domain. Methods: An electronic search was conducted using Elsevier's Scopus database. From a total of 940 retrieved papers (published between 2019 and 2024), 493 were selected. For data analysis and visualization, the titles of articles, year of publication, countries, authors, journals, articles, and keywords were analyzed using Microsoft Excel, VOSviewer, and Biblioshiny. Results: China published the most papers (200 articles) and received the highest number of citations, followed by the USA. While some countries, such as Egypt and India, published exclusively Single Country Publications (SCPs), others demonstrated a higher level of international collaboration, with at least half of their publications being Multi-Country Publications (MCPs). Countries with higher rates of MCPs were Greece (66.6%), Italy (53.8%), Korea, and France (50%). The journals that produced the most publications and received the highest number of citations were Cancers, International Journal of Molecular Sciences, and Frontiers in Oncology, confirming their role in producing high-impact research. Conclusions: The consistent distribution of publications over the years considered indicates a sustained interest in this field.